Strategi Pengembangan Usahatani Nenas Di Desa Doda Kecamatan Kinovaro Kabupaten Sigi - Wira Hatmi (AgriHumanis: Journal of Agriculture and Human Resource Development Studies, 2022)
Pineapple farming development strategy in Doda Village, Kinovaro District, Sigi Regency. This research aims to find out: 1) income level of pineapples farms in Doda Vilage, Kinovaro Subdistrict, Sigi District” 2) determine the development strategy of pineapples farm in Doda Vilage, Kinovaro Subdistrict, Sigi District. Population in this research was 30 pineapples farmers, and the sample was taken through purposive sampling. The data of research were obtained through observation, interview, questionnaires, and Focus Group Discussion. Data was analyzed by using SWOT analysis. The result of the research found out that the income of the peanepples farmers was at average Rp 3.546.420/0,81ha/MP Then for the determination of strategy development is WO (Weaknesis – Opportunities) supports the strategy turnaround with the formulation of the strategy 1). Give guidance to farmers about increased production of pineapples. 2) Provide skills training in managing their pineapple be processed products. 3). Increase marketing activities by relying on geographical location the village of Doda is located. 4) Improve quality of fruit pineapples in meeting market demand. 5) perform maintenance intensive plants to increase production of pineapples. The implementation, in the form a program that can be applied is 1). Application of technology cultivation pineapple farming to maximize production. 2) maximize the use of land to expand farming. 3. increase the added value of) the fruit of pineapple. 4) Streamline the rural transport. 5). Improving road infrastructure and facilities, 6). Application of technology of pre harvest and post harvest. 7) works closely with the College to conduct research